2022
DOI: 10.3390/w14040654
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Water-Quality Index for High Andean Basins: Application to the Chumbao River, Andahuaylas, Peru

Abstract: The water from the high Andean rivers is peculiar due to its composition and the geomorphology of its sources, and naturally or anthropogenically contamination is not discarded along its course. This water is used for agriculture and human consumption, therefore knowing its quality is important. This research aimed to proposing and formulate a water-quality index for high Andean basins through the Delphi method, and its application in the Chumbao River located in Andahuaylas-Peru. Forty-three water-quality par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The metrics based on trophic characteristics were highly correlated with the BMWP/Col and ABI indices. Therefore, these indices can be used to estimate river water quality and provide information on its functioning 7 SC Choque-Quispe, D. et al [ 68 ] Proposal of a Water-Quality Index for High Andean Basins: Application to the Chumbao River, Andahuaylas, Peru 2022 Formulate a water-quality index for a high Andean River through the Delphi method, taking it as an application case the river of the Chumbao micro-basin, Andahuaylas, Apurímac, Peru, covering the seasons 2018 to 2021. The application of WQIHA in the water from the high Andean basin of the Chumbao river showed that the areas surrounding the head of the basin present good quality, and they are not threatened, showing levels close to the natural state, and that it is rarely seen.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The metrics based on trophic characteristics were highly correlated with the BMWP/Col and ABI indices. Therefore, these indices can be used to estimate river water quality and provide information on its functioning 7 SC Choque-Quispe, D. et al [ 68 ] Proposal of a Water-Quality Index for High Andean Basins: Application to the Chumbao River, Andahuaylas, Peru 2022 Formulate a water-quality index for a high Andean River through the Delphi method, taking it as an application case the river of the Chumbao micro-basin, Andahuaylas, Apurímac, Peru, covering the seasons 2018 to 2021. The application of WQIHA in the water from the high Andean basin of the Chumbao river showed that the areas surrounding the head of the basin present good quality, and they are not threatened, showing levels close to the natural state, and that it is rarely seen.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Sample analysis was done according to (Quispe et al, 2022) which included: turbidity, total solid (TS), total dissolved solid (TDS), total suspended solid (TSS), hardness, biological oxygen demand (BOD), chemical oxygen demand (COD), nitrate (No3 -1 ), phosphate (Po4 -2 ), sulfate (So4 -1 ), and analysis of some heavy metals (Na, K, Pb, Cu, Cd, Ni). Biological analysis included total plate count (TPC), total coliform (TC), total fecal coliform (TFC) and fungi analysis.…”
Section: Analysis Of Samplesmentioning
confidence: 99%
“…The early detection of worrying trends in water quality is the only way to identify the adverse effects of pollution and apply corrective and preventive measures [10]. Source water monitoring should become one of the main strategies [11]. One tool to assess water quality [12] is the Water Quality Index (WQI), based on a combination of physical, chemical, and biological factors, which are condensed into a single value ranging from 0 to 100 [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%